Customers’ Awareness of Corporate Social Responsibility in Vietnam and Poland: a Comparative Analysis - Doanh, Duong Cong; Gadomska-Lila, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
Corporate Social Responsibility (CSR) has become one of emerging issues in such countries as Vietnam and Poland and in the rest of the world. This is due to the advantages it brings to socio‑economic sustainable development or the living environment. The focus of this research is to present a comparative analysis of the current understanding, awareness and attitudes of Polish and Vietnamese customers. The study employs quantitative analyses and some tools of descriptive statistics to show that although Vietnamese and Polish customers have a rather positive attitude towards the issues related to CSR, they are still not interested in CSR reports on companies’ reputation and image as well as environmental pollution. Moreover, customers also pay attention to low prices rather than the CSR reputation of companies. By utilising the Mann‑Whitney U Test, this study shows that even though both countries are seen as transitional economies, there are certain differences in attitudes towards and awareness of CSR activities between Vietnamese and Polish customers.